Baseball Players Exhibit Symptoms of Posttraumatic Stress Disorder After Ulnar Collateral Ligament Rupture (124). Issue 10 (31st October 2021) - Alexander, Frank; Anderson, Forrest; Anderson, Matthew; Spataro, Michelle; Skaggs, Kira; Swindell, Hasani; Ahmad, Christopher
Objectives: The significant psychological impact and prevalence of posttraumatic stress disorder (PTSD) have been thoroughly documented in multiple investigations of patients after anterior cruciate ligament ruptures, but this has not yet been assessed in patients after ulnar collateral ligament (UCL) rupture. Our hypothesis is that symptoms of PTSD are present among baseball players after UCL injury. Methods: Baseball players, from the high school to minor league baseball level who had suffered an acute UCL rupture were recruited at a tertiary care center. Patients completed the Horowitz Impact of Event Scale - Revised (IES-R) to analyze for PTSD symptomatology. Results: A total of 24 patients were enrolled. The mean patient age was 19.2 years (range 15-24 years). Twenty patients (83.3%) were pitchers; 12 pitched exclusively. Six patients surveyed played at the high school level (25%), 15 in college (62.5%), and 3 at the minor league level (12.5%). 100% of patients were male. Over 91% of patients experienced symptoms of intrusion, 87.5% displayed avoidance symptoms, and 79.2% had symptoms of hyperarousal. Twelve patients (50%) scored >24 on the IES-R (PTSD is a clinical concern). 6 patients (25%) reached the threshold for a probable diagnosis of PTSD (³33 on the IES-R). Conclusions: Following UCL rupture, athletes experience substantial emotional trauma, and a significant proportion of patients experience symptoms severe enough to warrant a diagnosis of PTSD.